"We almost had the whole block's phone number on the wall": A mixed methods investigation of informal helping in a predominantly rural sample. Issue 3 (3rd October 2018) - Hagler, Matthew; Hamby, Sherry; Banyard, Victoria; Grych, John
Abstract: Community psychologists have noted the limitations of professional models of mental health treatment, demonstrating that people are more likely to use informal familial or community support during adversity. However, relatively little is known about the forms and functions of informal help seeking and provision. Semistructured interviews ( N  = 170), in which a sample of predominantly rural‐dwelling adolescents and adults described significant life experiences, were coded for instances of receiving help. Codes thematically categorized the type of adversity, role of the helper, and nature of the help received. Most participants (67.64%) reported the presence of at least one informal helper; only 8.82% of participants discussed receiving professional help. Chi‐square analyses suggested that the nature of the help received varied by the types of helper and adversity being experienced and that different helpers were more likely to aid with particular adversities. The presence of a nonfamilial, nonprofessional helper was associated with higher posttraumatic growth, generativity, and perceived social support.